YIELD AND QUALITY OF CAULIFLOWER DEPENDING ON THE NORMS OF LIQUID COMPLEX FERTILIZERS (LCF 3:18:18) - Dydiv О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
Сauliflower demands proper soil fertility, as well as provision of macro- and microelements. A high yield of cauliflower is obtained on fertile, loamy soils, with a pH close to neutral. Due to a violation of the balance of mineral substances in the soil and a lack of moisture, plants lag in growth. Liquid complex fertilizers (LCF 3:18:18) are one of the effective mineral fertilizers from an ecological point of view, which are easily absorbed by plants. In conditions of the Western Forest Steppe of Ukraine, studies were conducted on dark gray podzolic light loamy soils to examine the influence of different rates of liquid complex fertilizers (LCF 3:18:18) on the yield and biochemical composition of cauliflower. A hybrid of cauliflower Lecanu F1 was chosen as the subject of the research. The scheme of the experiment included the following versions: 1) Control (without fertilizers); 2) LCF – 40 l/ha; 3) LCF – 80 l/ha; 4) LCF – 120 l/ha; 5) LCF – 160 l/ha; 6) LCF – 200 l/ha. For two years of research, a long width (17–18 cm) and weight of heads (1380 and 1460 g), density of 8 and 9 points, were obtained on the versions: LCF – 160 l/ha and LCF – 200 l/ha, while in the control version (without fertilizers) these figures were the lowest and amounted 13 cm and 620 g, respectively. Having applied the seedling method of growing cauliflower using the liquid complex mineral fertilizer (LCF 3:18:18) at the rate of 120 l/ha (LCF) and 160 l/ha (LCF), one obtained the high yielding capacity of cauliflower heads (42.6 and 47.1 t/ha), which exceeded the control (without fertilizers – 29.7 t/ha) by 12.9 and 17.4 t/ha, respectively. It was found that the increased rates of liquid complex fertilizers (LCF 3:18:18) of 200 l/ha did not contribute to a significant increase in yielding capacity. Liquid complex mineral fertilizers (LCF 3:18:18) improved the quality of cauliflower heads, in particular, one obtained the highest content of dry matter (9.38 %), total sugar (4.72 %), ascorbic acid (62.82 mg/%), protein (2.84 %) in version 4 at (LCF) a rate of 120 l/ha. The content of nitrate nitrogen in all versions of the experiment did not exceed the maximum allowable concentration. The content of nitrate nitrogen in all variants of the experiment did not exceed the maximum permissible concentration (MPC). There is a suggestion to apply a liquid complex mineral fertilizer (LCF 3:18:18) at a rate of 160 l/ha) to obtain a high yielding (47 t/ha) capacity with good quality of cauliflower heads of the hybrid Lecanu F1. One should apply the seedling method of cultivation on dark gray podzolic soils in the Western Forest-Steppe of Ukraine.